2019
DOI: 10.1186/s12871-019-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of effects of scalp nerve block and local anesthetic infiltration on inflammatory response, hemodynamic response, and postoperative pain in patients undergoing craniotomy for cerebral aneurysms: a randomized controlled trial

Abstract: Background The purpose of this study was to compare the effects of scalp nerve block (SNB) and local anesthetic infiltration (LA) with 0.75% ropivacaine on postoperative inflammatory response, intraoperative hemodynamic response, and postoperative pain control in patients undergoing craniotomy. Methods Fifty-seven patients were admitted for elective craniotomy for surgical clipping of a cerebral aneurysm. They were randomly divided into three groups: Group S (SNB with 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
68
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 38 publications
6
68
2
1
Order By: Relevance
“…We found in our study that postoperative hypertension and tachycardia (increase in MAP and HR) in response to craniotomy were signi icantly atten-uated for long duration during the postoperative period in group B compared to group C where there was a more prominent hyperdynamic response. Our results were in agreement with the research introduced by Yang et al (2019). In which the hemodynamic response and postoperative pain were assessed after regional scalp block in patients performing craniotomy for the repair of cerebral arteriovenous malformations, but it was different from our study in terms of that the local anaesthetic used was ropivacaine instead of lidocaine/bupivacaine mixture in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found in our study that postoperative hypertension and tachycardia (increase in MAP and HR) in response to craniotomy were signi icantly atten-uated for long duration during the postoperative period in group B compared to group C where there was a more prominent hyperdynamic response. Our results were in agreement with the research introduced by Yang et al (2019). In which the hemodynamic response and postoperative pain were assessed after regional scalp block in patients performing craniotomy for the repair of cerebral arteriovenous malformations, but it was different from our study in terms of that the local anaesthetic used was ropivacaine instead of lidocaine/bupivacaine mixture in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Lidocaine 2% / bupivacaine 0.5% 1:1mixture and epinephrine 1/200000 has been used in our study instead of lidocaine alone; that was used in the research introduced by Yang et al (2019); to avoid the occurrence of local anaesthetic toxicity and prolong the duration of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the lower incidence of PONV in the ERAS group was related to less intraoperative remifentanil consumption and postoperative analgesics use. This may be another reason for improving PONV [37]. In addition, multivariate analysis revealed that preoperative mouth-rinsing (Compound Chlorhexidine Gargle) and PONV prophylaxis were independent predictors for a lower incidence of vomiting on POD 2 in all patients ( Table 6).…”
Section: Discussionmentioning
confidence: 95%
“…The practice points for instituting a protocol for and the bene ts Scalp blocks provide better attenuation of in ammatory and hemodynamic response to craniotomyand better postoperative analgesia than incision site in ltration with local anesthetics (LA). (18) This, along with the addition of upiritine, a centrally-actingnonopioid analgesic, with selective action on neuronal potassium channels (Kv7), resulted in signi cantly improved post-surgical VAS cored in GrE. Flupiritine has been used previously in patients undergoing craniotomy to reduce pain and anxiety perioperatively.…”
Section: Discussionmentioning
confidence: 99%